Gastrointestinal Complications in Critically Ill Patients With COVID-19. Issue 2 (August 2020) - Kaafarani, Haytham M. A.; El Moheb, Mohamad; Hwabejire, John O.; Naar, Leon; Christensen, Mathias A.; Breen, Kerry; Gaitanidis, Apostolos; Alser, Osaid; Mashbari, Hassan; Bankhead-Kendall, Brittany; Mokhtari, Ava; Maurer, Lydia; et al.
Abstract : Supplemental Digital Content is available in the text